Design estratégico e mercado da fé: estudo de caso: Igreja Universal do Reino de Deus - Hagel Neto, Walter (Universidade do Vale do Rio dos Sinos, 2010)
This work describes the analysis of the strategies of building experience of the Universal Church of the Kingdom of God (IURD) through a case study conducted that included an ethnographic study and field research to demonstrate the correlation of the organization with the concepts of Strategic Design and Experience Design. The research included several aspects of the experience, such as experiential platform, the interface with the church-goer and the brand, innovation and environmental analysis. That study proved that the IURD is a complex organization, with corporate structure that is able to identify the needs of their users and turn them into an efficient product-system which is able to keep loyal users.
Keywords: Design estratégico; Experiência; Igreja Universal do Reino de Deus; Strategic design; Experience; Universal Church of the Kingdom of God; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial